Patent urachus rupture in calf - Kaewprom, Napong (Journal of Mahanakorn Veterinary Medicine, 2024)
A 2-month-old male Brahman calf was brought to the Large Animal Teaching Hospital at Mahanakorn University of Technology. The patient presented lethargic, anorexia, non-weight bearing, and bloated abdomen for 3 days. From physical examination, the symmetrical bloating and the fluctuation of the abdomen as well as 8-10% dehydration were found. Trans-rectal ultrasonography revealed that the urinary bladder was surrounded by fluid, the urine was less than normal, and the urinary bladder wall was thick. Abdominocentesis showed that fluid was clear-yellow with an ammonia smell. The hematology and blood chemistry results showed acute inflammation, and high levels of both blood urea nitrogen (BUN) and creatinine. The initial diagnosis identified urinary bladder rupture which caused the urine leak into the abdomen. The surgery was performed to find the cause of Uroabdomen and the patent urachus rupture was found. Then, the surgical correction was needed to resect the patent urachus. Amoxicillin and Flunixin-meglumine were used for postoperative cares to prevent the secondary infection and the pain, respectively. After the surgery, the calf was able to urinate via genital organ and recovered completely.